Correlation Between Polymer Packing And Gas Transport Properties For Co2/N2 Separation In Glassy Fluorinated Polyimide Membrane - Tan, P. C.; Jawad, Z. A.; Ooi, B. S.; Ahmad, A. L.; Low, S. C. (Taylor's University, 2016)
Gas separation performance of a membrane highly hinges on its physical properties. In this study, the interplay between polymer packing of a membrane and its gas transport behaviours (permeability and selectivity) was investigated through a series of 6FDA-DAM:DABA (3:2) polyimide membranes with different polymer compactness. The chemical structure and the polymer packing of the resulting membrane were characterized using attenuated total reflectance-Fourier transform infrared spectroscopy (ATR-FTIR) and packing density measurement, respectively. CO2/N2 separation efficiency of the membrane was evaluated at 25oC with feed pressure up to 6 bar. N2 permeability was found to rely on the membrane’s packing density, which signified its greater dependence on molecular sieving. In contrast, sorption showed a more vital role in determining the CO2 permeability. In this work, the membrane with a final thickness of 97±2 μm had successfully surpassed the Robeson’s 2008 upper bound plot with a CO2 permeability of 83 Barrer and CO2/N2 selectivity of 97 at 3 bar permeation.